Diversity and abundance of phytoplankton in Bone Bay, South Sulawesi, Indonesia and its relationship with environmental variables - RAHMADI TAMBARU; ANDI I. BURHANUDDIN; ABDUL HARIS; MUHAMMAD A. AMRAN; ARNIATI MASSINAI; AMIR HAMZAH MUHIDDIN; KHUSNUL YAQIN; FIRMAN FIRMAN; YULIANA YULIANA (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Tambaru R, Burhanuddin AI, Haris A, Amran MA, Massinai A, Muhiddin AH, Yaqin K, Firman, Yuliana. 2024. Diversity and abundance of phytoplankton in Bone Bay, South Sulawesi, Indonesia and its relationship with environmental variables. Biodiversitas 25: 624-631. Ecological studies of phytoplankton have been widely conducted in various bays around the world. However, such research is still limited in Bone Bay, South Sulawesi, Indonesia. Therefore, this study aimed to investigate the diversity and abundance of phytoplankton in Bone Bay and the relationships with environmental factors. Data collection was conducted in the dry season (May to June 2023) at four stations, namely Bajoe Harbor (PB), Cappa Ujung (CU), Libureng (LB), and Tongke-Tongke (TT). At each station, seawater samples were collected and environmental variables were measured including temperature, salinity, pH, currents, and nutrients (i.e. Nitrate, Nitrite, Ammonium, Orthophosphate, and Silicate). In general, the environmental variables in the studied area were within the range of optimal condition for phytoplankton to grow and develop. There were three classes of phytoplankton recorded, namely Bacillariophyceae, Cyanophyceae, and Dinophyceae, with a total of 31 genera were identified. Chaetoceros, Thallasionema, and Rhizosolenia were the dominant genera. The average abundance of phytoplankton was significantly different among stations with the highest was found in CU and PB compared to that in LB and TT (p-value <0.01). PCA analysis showed that phytoplankton abundance was related to high orthophosphate concentrations, silicate, and turbidity at the PB and CU stations, while the opposite condition occured at the LB and TT stations. Based on the diversity and abundance of phytoplankton, Bone Bay, South Sulawesi is now still in good condition, yet monitoring studies are recommended to see the changes in the future.